The concentration of cleared derivatives: Can access to direct CCP clearing for end-users address the challenge? - Nahiomy Alvarez; John McPartland (Federal Reserve Bank of Chicago, 2019)
Cleared derivatives contracts are now concentrated among a small and dwindling number of institutions. Many policymakers and regulators have argued that this concentration has adverse consequences, some of which may have systemic risk implications. The authors explore the benefits and challenges of encouraging major end-users of derivatives to become direct clearing members of central counterparties (CCPs). If done prudently, increasing and diversifying the pool of clearing members and redistributing outstanding derivatives contracts across them may help CCPs become more resilient.
Keywords: 330